MS analysis of single-nucleotide differences in circulating nucleic acids: application to noninvasive prenatal diagnosis - Ding, C.M.; Chiu, R.W.K.; Lau, T.K.; Leung, T.N.; Chan, L.C.; Chan, A.Y.Y.; Charoenkwan, P.; Ng, I.S.L.; Law, H.Y.; Ma, E.S.K.; Xu, X.M.; Wanapirak, C.; et al. (2004)
The analysis of circulating nucleic acids has revealed applications in the noninvasive diagnosis, monitoring, and prognostication of many clinical conditions. Circulating fetal-specific sequences have been detected and constitute a fraction of the total DNA in maternal plasma. The diagnostic reliability of circulating DNA analysis depends on the fractional concentration of the targeted sequence, the analytical sensitivity, and the specificity. The robust discrimination of single-nucleotide differences between circulating DNA species is technically challenging and demands the adoption of highly sensitive and specific analytical systems. We have developed a method based on single-allele base extension reaction and MS, which allows for the reliable detection of fetal-specific alleles, including point mutations and single-nucleotide polymorphisms, in maternal plasma. The approach was applied to exclude the fetal inheritance of the four most common Southeast Asian beta-thalassemia mutations in at-risk pregnancies between weeks 7 and 21 of gestation. Fetal genotypes were correctly predicted in all cases studied. Fetal haplotype analysis based on a single-nucleotide polymorphism linked to the beta-globin locus, HBB, in maternal plasma also was achieved. Consequently, noninvasive prenatal diagnosis in a mother and father carrying identical beta-thalassemia mutations was accomplished. These advances will help in catalyzing the clinical applications of fetal nucleic acids in maternal plasma. This analytical approach also will have implications for many other applications of circulating nucleic acids in areas such as oncology and transplantation.